Influence of gauge width on rail side wear on track curves - Povilaitienė, Inesa; Kamaitis, Ipolitas Zenonas; Podagėlis, Igoris (Journal of Civil Engineering and Management, 2006)
The main property of the railway system is infrastructure objects and rolling‐stock. Holding any kind of a property requires huge expenses and renovation investments. Intensive wearing of the rails on the track curves is observed. This problem is always topical in railways. In this article a possibility to decrease wear of rails on curves is analysed. The purpose of the authors’ research was to estimate the influence of rail wearing on the track widening and permissible deviations on curves when radius is less than 650 m. Also, to estimate the possibility to reduce railroad maintenance expenses associated with the change of the worn rails, when gauge on curves with radius less than 650 m is widened. For this reason in this article a mathematical model is presented. This model evaluates the influence of the gauge width on rail wearing on curves. An experiment was carried out on Lithuanian railway line curves. Results and analysis of the experimental research are presented in the article.Geležinkelio vėžės pločio įtaka bėgių šoniniam dilimui kreivėseSantrauka. Pagrindinis geležinkelio sistemos turtas yra infrastruktūros objektai ir riedmenys. Jiems išlaikyti reikia didelių išlaidų, o renovacijai – investicijų. Straipsnyje nagrinėjama nuolat aktuali geležinkelio problema – tai bėgių dilimo mažinimo galimybė kreivėse. Autorių tyrimo tikslas yra nustatyti, kaip vėžės platinimas ir leistinieji nuokrypiai daro įtaką bėgių dilimui kreivėse, kurių spindulys mažesnis nei 650 m. Apskaičiuota, kiek sumažėtų geležinkelio priežiūros išlaidos, susijusios su nudilusių bėgių keitimu kreivėse, kai kelio vėžė kreivėse, kurių spindulys mažesnis nei 650 m, platinama pagal pateiktus siūlymus. Tam tikslui straipsnyje pateikiamas matematinis modelis. Šiuo modeliu įvertinama vėžės pločio įtaka bėgių dilimui kreivėse. Eksperimentiniai tyrimai buvo atlikti Lietuvos geležinkelio linijų kreivėse. Pateikiama eksperimentinių tyrimų rezultatų analizė.Raktiniai žodžiai: geležinkelis, bėgis, bėgio nuodyla, vėžės plotis, kreivė, bėgio dilimo intensyvumas, ratų antbriaunis.First Published Online: 14 Oct 2010